Analisis Penggunaan Virtual Background Seragam di Pertemuan Daring menggunakan Teknik Coding Kualitatif - M. Daffas Athadiansyah; Diah Priharsari; Satrio Hadi Wijoyo (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Online meeting activities are carried out by some people because of the Covid-19 pandemic. Meeting activities that should be done in person can be done using online meetings. There are several applications to conduct online meeting activities, one of the applications that has many users, namely ZOOM. The application has a high level of use because of the many features and the use of features is quite easy. Among some of the features provided by ZOOM, a feature that is often used by the public is the virtual background feature. The use of virtual background by the public is usually to attend online meetings, scientific seminars, organizing events, and other events by making virtual backgrounds between participants uniform. The use of virtual background uniforms in online meeting activities is also not yet known because events held online are usually tied to the use of virtual background uniforms. The data collection in this study was carried out qualitatively to active users of uniform virtual backgrounds by conducting semi-structured interviews. The results of the interview obtained are then analyzed using thematic analysis methods and obtained results related to background using and not using virtual background uniforms and how the speakers view online meeting activities using virtual background uniforms and do not use virtual background uniforms.